THE MIGRANT OTHER: EXCLUSION WITHOUT NATIONALISM? - Schenk, Caress (Cambridge University Press, 2021)
Migrants are an easy, visible Other, seeming to fall neatly into the us-versus-Them framework of nationalism. Nevertheless, much of the scholarly approach to migrant identity, with the partial exception of a largely separate literature on citizenship, has eschewed overt ties to nationalism studies. When us-versus-Them language is used in relation to nationalism, the focus or nodal point is the identity of the seemingly homogenous us of the nation. However, when migrants are othered, the focus is not always the nation, and while othering migrants always creates exclusion, it is not always exclusion from a nation or identity group. This state of the field article analyzes the literature on populism, securitization, biopolitics, and other critical scholarship related to the issue of othering migrants. In each of these bodies of work, different sets of us are set against migrants, some of which evoke identity and others of which do not, elucidating the links (or the lack thereof) of each approach to the study of nationalism. In each of these frameworks, the migrant Other comes up against a different frame of reference, leaving migrants themselves (or any sense of migrant identity) somewhat lost amid the analytical frameworks, at continual risk of being re-othered as victims of circumstance without agency.
Keywords: biopolitics; migration; populism; securitization; Type of access: Open Access